Health insurance coverage and access to maternal healthcare services by women of reproductive age in Nigeria: a cross-sectional study - Adeleye Abiodun Adeomi; Oluwaseun Taiwo Esan; Olusegun Temitope Afolabi (BMJ Publishing Group, 2023)
Background Inequitable financial access to maternal healthcare services (MHS) has contributed to maternal deaths, especially in low and middle-income countries. Evidence in the literature on women's health insurance status and access to MHS in Nigeria is sparse. This study aimed to determine the association between health insurance coverage and access to MHS among Nigerian women of reproductive age.Methods This is a cross-sectional study that used the 2018 Nigeria Demographic and Health Survey (NDHS). A total of 12 935 women who had their last delivery within 2 years before the NDHS were included in the study. Access to MHS was assessed by using the number of antenatal care (ANC) visits and health facility delivery. Adjusted logistic regression models were fit to control for individual, household and community-level factors.Results Only 18.5% and 40.6% of the women in the study attended ≥8 ANC visits and delivered in a health facility, respectively. About 39.5% of women who had ≥8 ANC visits and 71.8% of those who delivered in health facilities had health insurance coverage. There were statistically significant associations between having health insurance and attendance of ≥8 ANC visits (adjusted OR (AOR) 1.9; 95% CI 1.26-2.95) and women delivering at a health facility (AOR 2.0; 95% CI 1.39-2.82). There were also lower significant odds of accessing ≥8 ANC visits and delivering in health facilities among the rural dwellers, unemployed, those with lower educational status and those in the lower social economic quintiles.Conclusion There was a low uptake of health insurance programmes among the Nigerian women in this study. Having health insurance coverage was significantly associated with ≥8 ANC visits and women delivering in health facilities. Thus, providing health insurance may be an important way to improve women's access to MHS in Nigeria.